Deconstructing divergent constructions of illicit drug use and drug-using subjects: understanding enduring stigma and marginalisation - Willis, Laura Lehane (Curtin University, 2016)
In this research deconstructive analyses of news-media texts and interview data were conducted to explore divergences in western liberal constructions of illicit drug use and drug-using subjects, and the stigmatising and marginalising effects of such constructions. The findings pose questions about the role that dichotomising knowledge practices and underlying affective processes may play in limiting the development of meaningful and effective changes in how such conduct and individuals are understood and approached in western liberal culture.